2022
DOI: 10.3390/d14110935
|View full text |Cite
|
Sign up to set email alerts
|

Taxonomic Reassessment of Freshwater Mussels from the Western Balkans Reveals an Overlooked but Critical Refugium and Defines Conservation Priorities

Abstract: Freshwater mussels are an endangered group of animals, especially in the water bodies of Central and Western Europe. Conservation priorities were established for many endangered freshwater mussel species in the last decade. Here, we present new data on a cryptic refugium of freshwater mussels in the Western Balkans. Two species, Anodonta exulcerata Porro, 1838 and Unio elongatulus Pfeiffer, 1825, were discovered in Montenegro for the first time. The phylogenetic position and taxonomic status of freshwater muss… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 55 publications
0
0
0
Order By: Relevance
“…It was observed that this species is generally vulnerable to environmental degradation, especially to changes in water chemistry [14]. The high level of eutrophication caused by agricultural drainage is considered to be the main reason for the decline of U. crassus [10,22,30,[52][53][54]. Our data show that the mean nitrate-nitrogen concentration varies between the study periods (Figures 7 and 8).…”
Section: Discussionmentioning
confidence: 59%
“…It was observed that this species is generally vulnerable to environmental degradation, especially to changes in water chemistry [14]. The high level of eutrophication caused by agricultural drainage is considered to be the main reason for the decline of U. crassus [10,22,30,[52][53][54]. Our data show that the mean nitrate-nitrogen concentration varies between the study periods (Figures 7 and 8).…”
Section: Discussionmentioning
confidence: 59%
“…The data obtained by the authors confirm that Unionicola mites are narrow host specialists that are associated with either one or a few closely related freshwater mussel species belonging to one or two sister genera. The taxonomic reassessments of freshwater mussels based on an integrative approach were performed by Lyubas et al [6] on the Western Balkans. Authors present a new data on a cryptic refugium of freshwater mussels in this region.…”
Section: Taxonomy Phylogeny and Evolutionmentioning
confidence: 99%